Inhibitory effect of salmeterol on the respiratory burst of adherent human neutrophils - OTTONELLO, L (Blackwell Science Inc, 1996)
Human neutrophils, plated in fibronectin-coated wells and stimulated with n-formyl-methionyl-leucyl-phenylalanine (fMLP), were found to undergo a massive and prolonged respiratory burst, as measured by monitoring superoxide production. The β(2)-agonist salmeterol inhibited the respiratory burst in a dose-dependent manner. In contrast, salbutamol was ineffective. Moreover, the neutrophil respiratory burst was partially suppressed by prostaglandin E(2) (PGE(2)) and the phosphodiesterase type IV (PDE-IV) inhibitor RO 20-1724. When salmeterol was used in combination with PGE(2) or RO 20-1724, additive inhibitory effects were observed. The inhibitory activity of salmeterol was not reversed in the presence of the β-blocker propranolol, and did not correlate with its ability of increasing cyclic AMP (cAMP) levels. Finally, the compounds used did not affect neutrophil adherence to fibronectin-coated wells. The results suggest that salmeterol is capable of down-regulating the neutrophil oxidative response to fMLP, also of co-operating with PGE(2) and PDE-IV inhibitor RO 20-1724 in a manner not related to its β(2)-receptor binding activity. In other words, salmeterol displays neutrophil-directed effects, susceptible to be amplified by natural mediators such as PGE(2) or PDE-IV inhibitors, consistent with possible anti-inflammatory properties of the drug.